Enhancement of methane production in anaerobic digestion of high salinity organic wastewater: The synergistic effect of nano-magnetite and potassium ions. (March 2023) - Guan, Qiuyue; Qu, Yunhe; Zhai, Yujia; Shi, Wansheng; Zhao, Mingxing; Huang, Zhenxing; Ruan, Wenquan
Abstract: During high salinity organic wastewater (HSOW) anaerobic digestion treatment, the process of methanogenesis can be severely inhibited in the high salinity environment, and the accumulation of volatile organic acids (VFAs) leads to failure of the anaerobic reaction. In this study, nano-magnetite and KCl were adopted to alleviate the inhibitory effect of high salinity and enhance the HSOW anaerobic digestion performance. The result showed that, under the optimal dosage of 200 mg/L, nano-magnetite addition promoted the anaerobic digestion performance, and the methane production increased by 11.06%. When KCl was added with a dosage of 0.174%, the methane production increased by 98.37%. The simultaneous addition of nano-magnetite (200 mg/L) and KCl showed a synergistic effect on enhancing HSOW anaerobic digestion performance, and the methane production increased by 124.85%. The addition of nano-magnetite and KCl promoted the conversion of VFAs, especially accelerated the degradation of propionic acid and butyric acid, also it promoted the activity of acetate kinase, dehydrogenase and F420, and thereby enhanced the methanogenesis process. This study could provide a new method for enhancing the anaerobic digestion of HSOW. Graphical abstract: Image 1 Highlights: Nano-magnetite and KCl were added to enhance HSOW anaerobic digestion performance. CH4 production increased by 11.06% under optimal dosage of 200 mg/L nano-magnetite. Nano-magnetite and KCl showed a synergistic effect on enhancing CH4 production. Nano-magnetite and KCl addition promoted VFAs conversion and key enzyme activity.